Fixed-dose combination antihypertensives in patients with chronic kidney disease: A systematic literature review - Vedad Herenda; Selma Jusufović; Adnan Musanović (Medicinski glasnik, 2025)
Aim: To systematically review the efficacy and safety of fixed-dose combination (FDC) antihypertensive agents in chronic kidney disease (CKD). Methods: This systematic review included studies from January 2014 to December 2023 that evaluated FDC antihypertensives in CKD. We searched The PubMed, Embase, and the Cochrane Library databases were searched. Inclusion criteria encompassed studies written in English and published in peer-reviewed journals. Exclusion criterias among others were review articles, editorials, letters, and conference abstracts. Results: Six studies met inclusion criteria from 1156 identified publications. Analyzed studies were included randomized trials (4), cohort studies (1), and retrospective analyses (1). FDCs improved medication adherence, blood pressure control, and renal outcomes. Significant blood pressure puni naziv skraćenice (BP) reductions were noted with FDCs compared with free combinations. FDCs of renin-angiotensin system inhibitors and thiazide diuretics showed improved adherence, reduced major adverse cardiovascular events, and better renal function preservation. Some combinations losartan hidrochlortiazid demonstrated a more significant reduction of proteinuria and urinary protein-to-creatinine ratio (UPCR), indicating potential renoprotective effects. Conclusion: While using FDC antihypertensives has shown promising results in improving patient outcomes in CKD, further large-scale, long-term randomized trials are urgently needed to confirm these findings and optimize treatment strategies. Keywords: cardiovascular diseases, hypertension management, medication adherence, proteinuria, renoprotection
Keywords: cardiovascular diseases; Hypertension Management; Medication Adherence; Proteinuria; Renoprotection